The Gambia - Recovering Fiscal Discipline : Public Expenditure Review - World Bank (Washington, DC, 2012)
Recent economic performance in The Gambia was extremely poor, and undermined efforts to implement the Poverty Reduction Strategy Paper (PRSP). Laxity in fiscal and monetary policies, and low agricultural production resulted in low growth, high inflation, and rapid depreciation of the domestic currency. Key macroeconomic targets in the PRSP were missed by a wide margin, and the International Monetary Fund (IMF) Poverty Reduction and Growth Facility (PRGF) program has been substantially off track. Past expansion of the money supply necessitates tight monetary policies in the form of higher interest rates, which have in turn increased public debt service, and crowded other public spending, including PRSP priority spending. The fiscal and debt sustainability analysis indicates that the country's fiscal situation is unsustainable if the current situation persists, particularly since the country continues to be vulnerable to exogenous shocks, such as the low rainfalls in 2002. The present Public Expenditure Review (PER) seeks to analyze the reform agenda, while mindful of local capacity and incentives. However, even if the agenda is carefully designed, in the end the success of the reform agenda depends on a high level o f political commitment. It should be noted, though, that the validity of the analysis is only as good as the underlying data. Unfortunately, the quality, reliability, and comprehensiveness of data are generally acknowledged problems in The Gambia. The present analysis points out that the actual expenditure data have internal inconsistencies that need to be resolved in order to fully validate the analysis. Recommendations are summarized as follows: reduced debt service through fiscal discipline should be a top priority; PRSP priorities need to be further reflected in the national budget; major imbalances within the budget structure need to be adjusted; the quality of data should be improved; development and commitment to a time bound action plan on the preparation, and auditing of public accounts should be a priority; cash budgeting should be phased out, in line with improved budget management practices; and, recurrent expenditures for the social sectors should be increased, particularly for the Education Sector.